Uso de una herramienta didáctica para la práctica de la entonación en hablantes no nativos de español - Pilar Oplustil; Gloria Toledo (Sintagma, 2019)
This study starts from the characterization of intonation of requests and orders in Chilean Spanish in order to create a computational teaching tool for Spanish as a foreign language (SFL) and to test this tool among 10 SFL learners. The characterization of intonation among Chilean speakers reveals differences between men and women for the speech acts which are the object of the present study. The application of the tool among SFL learners shows a greater difficulty in imitating the intonational pattern of orders for both men and women. Finally this study shows the effectiveness of the teaching tool, since 100% of the learners improved their production after using this didactic resource.